Enterprise risk management in Portugal - Pinto, C.; Azevedo, G.; Oliveira, J. (Enterprise risk management in Europe, 2020)
The present chapter tries to assess the state of art of Enterprise Risk Management (ERM) among Portuguese non-financial companies regarding two main aspects: the ERM background in Portugal and the level of disclosure of ERM practices by non-financial listed companies. Since the analysis of disclosures is useful to understand the level of evolution and adoption of ERM framework we tried to assess the ERM practices disclosed by 26 Portuguese non-financial listed companies at the Euronext Lisbon Stock Exchange regulated market, during the period of 2006-2016. Main findings indicate that regulation on ERM in Portugal emanates from three main Codes (The Portuguese Companies Code, The Stock Exchange Code, and The Corporate Governance Code). The ERM professionalization in Portugal is its infancy and has been promoted mainly by the Institute of Portuguese Internal Auditors. Moreover, research on topics such as risk reporting and risk management/ERM is very scarce. Overall, findings of prior literature are consistent with results from our exploratory study. We conclude that Portuguese non-financial listed companies still disclose very little information on ERM activities. However, over the period of analysis, the disclosure practices evolved positively. Findings show that ERM disclosure can still be extensively improved in the future.